17PDistance related outcome in indigenous and non-indigenous breast cancer women of Western Australia. (24th November 2019) - Khan, A; Martin, H; Spalding, L J; Redfern, A
Abstract: Background: In Australia, Indigenous people are natives and custodians of land. The mortality risk is more than double in Indigenous breast cancer women as compared to non- Indigenous women but carries lower incidence risk. Between 2001 and 2010 Indigenous Western Australian women who developed breast cancer were four times more likely to die of the disease than non-Indigenous women of the same age. The data is scarce but many factors are being studied. The effect of remoteness on mortality of indigenous women still needed to be established. The aim is to analyse remoteness as a factor causing effect on survival in Indigenous breast cancer women. Methods: The data is collected retrospectively from Western Australian cancer Registry mostly, among other sources. A cohort of 100 patients was selected from database including half of indigenous and half non-indigenous women (1:1). At time of writing, 37 Indigenous and 33 Non–Indigenous breast cancer women data was available. The data collected, to analyze the median survival time (months) of patients with respect to Distance (Metropolitan vs Rural) and Indigenous & Non-Indigenous status. Results: In survival analysis, it has been observed that both indigenous and non-indigenous who live in metropolitan showed better 10 year survival ; 184 months while who were in rural area showed reduced median survival time 130 months and differences among them was found to be significant (p = 0.03), suggesting better survival was associated with patients who live in metropolitan area. However, on analyzing the survival of Indigenous patients with respect to distance, it wasn't statistically significant (p = 0.19) but still showed higher median survival for patients living in metropolitan area (153 months) as compared to remote rural areas (110 months). Further analyzing indigenous breast cancer patients outcomes with respect to metro area (153 months), 1000km or less and greater then 1000km (87 months); higher survival benefit trend for patient's living close to metro area. Conclusions: The data suggest that the Indigenous breast cancer women have inferior survival outcomes with respect to distance from metropolitan area, highlighting a strong co-relation of remoteness and survival disadvantage. Legal entity responsible for the study: A. Khan, A. Redfern. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.